Strategic Exploration Mechanisms: Scaling, Alignment, and Efficiency in BIG-Bench Hard - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 10 peer-reviewed papers addressing the following research question: How does the strategic exploration mechanism introduced in this paper scale with model size and affect the trade-off between alignment quality and inference efficiency, evaluated using the BIG-bench. 10 claims were extracted from source literature; 4 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 6.5/10. This report
Machine-generated literature synthesis.